Corruption and Legislatures: Exploring Perceptions of Ukrainian Legislators. (3rd July 2020) - Khmelko, Irina; Bonnal, Michaël
Abstract : Corruption has remained one of the significant problems in post-authoritarian societies. While many of these countries have institutions in place to combat corruption, the corruption remains rampant. This article uses the case of Ukraine to search for an explanation for why there is a lack of political will to address the issue of corruption. Based on four waves of original survey data from the Ukrainian parliament, this article analyzes factors associated with observed legislative attitudes toward corruption. The findings of the analysis suggest that constituency representation, connections to oligarchs or related powerful economic interests, and membership in an opposition faction are all important predictors of how important the issue of corruption will be for legislators.